Factors that influence customers’ intention to purchase hybrid cars in Malaysia / Nur Erieana Sharil - Sharil, Nur Erieana (Faculty of Business and Management, 2019)
The purpose of this research paper is to study the factors that influence customers‟ intention to purchase hybrid cars in Malaysia. There are three factors that influence customers‟ intention to purchase hybrid cars in Malaysia which is cost, environmental concern and brand. These three factors are independent variables for this research while the dependent variable is customers‟ intention to purchase hybrid cars in Malaysia. Literature reviews have been used to support all the independent and dependent variables. Data is collected through a questionnaire distributed to 150 respondents located at Setia Alam. The sampling technique used was the non-probability sampling which is convenience sampling. Result of this research shows that there is significant relationship between cost, environmental concern and brand and customers‟ intention to purchase hybrid cars in Malaysia. Meanwhile, brand factor is the most influence toward customers‟ intention to purchase hybrid cars in Malaysia. Lastly, recommendations are made based on the results and suggestion in order to improve sales of hybrid cars.